(untitled) (European Bison Conservation Newsletter, 2008)
The history of European bison at Niepołomice falls back to medieval ages when this forest was a hunting ground for Polish kings. First breeding station for European bison was established there in 1938, but it was fully developed only since 1946. Animals belonging to mixed Lowland – Caucasian line were bred there until 1979, since then maintained there is a pure Lowland line. Animals from this breeding centre were used for numerous reintroductions in Poland including Bieszczady and Western Pomeranian population, as well as were send to foreign breeding centres. During 70 years of the existence of this centre 255 animals were born there. At present, the centre keeps 26 European bison.